Chemical modification of palm kernel shell filled polylactic acid biocomposite flims
In this research the effect of untreated and treated palm kernel shell (PKS) on the mechanical properties, morphological analysis and thermal properties of polylactic acid (PLA)/PKS biocomposite films were studied. The biocomposite films from palm kernel shell powder and polylactic acid were prepared from solution casting method where the PLA was dissolved in the chloroform and was stirred at 600 rpm, then the solution were casted inside the petri dish. The result showed that the increased in PKS content had decreased the tensile strength, elongation at break but had increased the modulus of elasticity. The glass transition temperature (Tg) and crystallinity (Xc) were the highest at 10 php filler content. The decomposition temperature at maximum (Tdmax) was raised with increased in PKS content The thermal stability was improved at high filler content because of lower total weight loss at 600 oC. SEM analysis showed that poor interfacial interaction between hydrophillic PKS and hydrophobic PLA matrix. The different types of chemical modification using butyl methacrylate (BMA), lactic acid (LA) and 3- mercaptopropyl-trimethoxy silane (3-MPS) were investigated in this study. The treated biocomposite films with BMA, LA and 3-MPS exhibited high tensile strength and modulus of elasticity, however, the elongation at break lowered compared to untreated biocomposite films. The chemical modification also enhanced the Tg and Xc of the treated biocomposite films. The FTIR analysis showed the chemical modification of PKS had reduced the hydroxyl group of PKS. Better interfacial adhesion and interaction between PKS and PLA matrix were proven by SEM study. Amongs all the chemical modification that been used, the chemical modification using BMA shows the highest properties incomparison with the used of LA and 3-MPS as chemical modification.